Friction in Adhesive Contact Between a Rough Hard Indenter and Smooth Soft Elastomer Layer - Iakov A. Lyashenko; Thao H. Pham; Valentin L. Popov (Machines)
The friction between a hard steel indenter and a soft elastomer is studied experimentally. To investigate the influence of roughness, a series of experiments was conducted utilizing an indenter with varying degrees of surface roughness. There is a strong adhesive interaction between the contacting bodies and the friction force is proportional to the real contact area. It has been shown that as the amplitude of roughness increases, the friction force initially rises due to the deformable elastomer filling the gaps between the roughness features, thereby increasing the real contact area. An increase in the roughness amplitude results in a more regular dependence of the friction force on the tangential displacement of the indenter. High-amplitude roughness prevents the propagation of elastic deformation waves (Schallamach waves) within the contact, which are responsible for the establishment of a “stick–slip” type of friction regime. The results of this study are of interest for technical applications in mechanical engineering, particularly those involving the production of rubber seals.